2005
DOI: 10.1136/gut.2004.054718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folic acid supplementation on genomic DNA methylation in patients with colorectal adenoma

Abstract: Background and aims: A low dietary folate intake can cause genomic DNA hypomethylation and may increase the risk of colorectal neoplasia. The hypothesis that folic acid supplementation increases DNA methylation in leucocytes and colorectal mucosa was tested in 31 patients with histologically confirmed colorectal adenoma using a randomised, double blind, placebo controlled, parallel design. Methods: Subjects were randomised to receive either 400 mg/day folic acid supplement (n = 15) or placebo (n = 16) for 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
182
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(186 citation statements)
references
References 38 publications
(26 reference statements)
1
182
0
2
Order By: Relevance
“…Genetic defects in methionine metabolism related to methionine synthase, N 5,10 -methylenetetrahyrdofolate, also result in neural dysfunction, mental retardation, and pregnancy complications (6)(7)(8). Recent studies have linked homocysteine, folate, and DNA methylation with gastrointestinal diseases, namely inflammatory bowel disease and colon cancer (9)(10)(11)(12)(13). The underlying mechanism linking homocysteine to inflammatory disease may be the induction of leukocyte adhesion molecules and proinflammatory cytokines in vascular endothelial cells (10).…”
mentioning
confidence: 99%
“…Genetic defects in methionine metabolism related to methionine synthase, N 5,10 -methylenetetrahyrdofolate, also result in neural dysfunction, mental retardation, and pregnancy complications (6)(7)(8). Recent studies have linked homocysteine, folate, and DNA methylation with gastrointestinal diseases, namely inflammatory bowel disease and colon cancer (9)(10)(11)(12)(13). The underlying mechanism linking homocysteine to inflammatory disease may be the induction of leukocyte adhesion molecules and proinflammatory cytokines in vascular endothelial cells (10).…”
mentioning
confidence: 99%
“…Although DHFR did not turn up any significant hits in the database search and miR-24 was not considered an miRNA of interest in this review (neither it is neural specific nor was it predicted to target Dll1, Dnmt1, Mthfr, or Rbl2), Mishra et al, 2004. showed that DHFR is targeted by miR-24, which was found to be upregulated 1.36 times greater than control in TK-6 cells grown in FAD media (Marsit et al, 2006). This suggests that folate deficiency could initiate a negative feedback loop where overexpression of miR-24 suppresses DHFR, which would further decrease methyl-donor pools, exacerbating methyl deficiency (Bohnsack and Hirschi, 2004;Pufulete et al, 2005;Fig. 4).…”
Section: Dhfrmentioning
confidence: 99%
“…The precursor cells for both neural crest cells and the neuroepithelial cells of the neural tube also have a higher level of folate receptor expression (Boot et al, 2003). Research has shown that folic acid levels directly correlate to genomic DNA methylation and deficiency is associated with global genomic hypomethylation, which is reversible with repletion therapy (Bohnsack and Hirschi, 2004;Choi et al, 2005;Pufulete et al, 2005;Rampersaud et al, 2000).…”
Section: Understanding the Causes Of Ntdsmentioning
confidence: 99%
See 2 more Smart Citations